A green method of reducing graphene oxide by tangerine peel extract - Hamid, Raghad Ali; Mohd Zawawi, Ruzniza (Asian Publication Corporation, 2024)
This work introduces a simple and environmental friendly approach for synthesizing reduced graphene oxide using tangerine peel extract as a non-toxic alternative to toxic compounds. Various microscopic and spectroscopic techniques were used to characterize the synthesized reduced graphene oxide. The UV-visible spectra of reduced graphene oxide (287 nm) at specific wavelengths and the FTIR analysis showed that the oxygen groups in reduced graphene oxide were reduced. Raman analysis confirmed a small increase in the intensity ratio of the D-band to the G-band. The X-ray diffraction spectra showed the presence of reduced graphene oxide in the 2θ angle, at 28.36ºpeak with a d-spacing value of 2.12 nm. The wettability and morphology of reduced graphene oxide were also investigated. The carbon-to-oxygen ratio of reduced graphene oxide was increased compared to graphene oxide in addition, the cyclic voltammetry was used to evaluate the electrochemical behaviour of the reduced graphene oxide.